1993
DOI: 10.1139/f93-259
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Elements Transported Upstream by Runs of Pacific Salmon: II. δ15N and δ13C Evidence in the Kvichak River Watershed, Bristol Bay, Southwestern Alaska

Abstract: Biota δ15N and δ13C values (deviations from recognized isotope standards) from lliamna Lake (a major anadromous sockeye salmon (Oncorhynchus nerka) nursery lake supporting peak-year runs > 10 million) and several other anadromous-salmon-free lakes in the Kvichak River watershed, Bristol Bay, southwestern Alaska, were compared to determine the significance of marine-derived nitrogen (MDN) delivered by returning adult salmon. Biota in lliamna Lake had higher δ15N compared with control lakes, verifying a mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
144
2
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(160 citation statements)
references
References 18 publications
5
144
2
9
Order By: Relevance
“…For example, Bilby et al (1998) found a positive relationship between marine derived nitrogen and smolt production. Similar observations have been made in individual river systems from Alaska to Washington (Piorkowski 1997, Larkin and Slaney 1997, Bilby et al 1996, Kline Jr. et al 1993, and Mathisen 1972.…”
Section: Ecological Significance Of Coho Salmon In the Clearwater Rivsupporting
confidence: 73%
“…For example, Bilby et al (1998) found a positive relationship between marine derived nitrogen and smolt production. Similar observations have been made in individual river systems from Alaska to Washington (Piorkowski 1997, Larkin and Slaney 1997, Bilby et al 1996, Kline Jr. et al 1993, and Mathisen 1972.…”
Section: Ecological Significance Of Coho Salmon In the Clearwater Rivsupporting
confidence: 73%
“…Nitrogen isotope ratios-Nitrogen isotopes can be used to trace the fate of marine-derived nitrogen through terrestrial and freshwater food webs (Kline et al 1993). Empirical relations between salmon nutrient loading and sediment d 15 N have been used to track historical variations in salmon spawner abundance in Alaskan lakes (Finney et al 2000;Finney et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At sexual maturity, they return to their natal stream to spawn and die (semelparity). Spawning salmon provide a source of nutrients for local predators and fertilize local aquatic ecosystems (for example, Kline et al 1993). Over-fishing, habitat loss, and poor marine survival have contributed to the decline of salmon returns to British Columbia, Canada, streams during the last century (Gresh et al 2000).…”
mentioning
confidence: 99%
“…Recently, between-lake variation in the 615N of piscivores has been proposed to distinguish lakes where high concentration of persistent contaminants in fish is attributable to longer than usual food chains from those where point-source contamination should be suspected (12). However, variation in the 615N signature of primary producers at the base of the food chain can produce variation in 815N within the same species of predator (13,14), independently of the length of food chain supporting the production of such top consumers. Thus, the general applicability of 815N as a time-integrated measure of variation of trophic level among populations of the same consumer species depends on our ability to first identify and measure betweenhabitat variation in the 815N signature of primary producers or that of other organisms with fixed low trophic level and then adjust the V5N values of consumers to these reference values so that their 615N truly reflect variation in trophic level and not variation in 815N at the base of the food chains.…”
mentioning
confidence: 99%
“…from Quebec and Ontario lakes are show as unlabeled solid circles (present study). 815N data sources: 1, S15N data for zebra mussel (Dreissena polymorpha) from Lake Oneida, United States, were kindly provided by E. L. Mills (Cornell University); 2, gizzard shad (Dorosoma cepedianum), a herbivorous fish (24) from Lake Erie, Canada (present study); 3, average for four species of herbivorous cladocerans and copepods (Eodiaptomusjaponicus, Bosmina sp., Diaphanosoma brachyurum, and Cyclops vicinus) from lake Kasumigaura, Japan, over 14 months (29); 4, average for six species of herbivorous zooplankton (Eodiaptomus japonicus, Bosmina fatalis, Bosmina longirostris, Bosminopsis dietersi, Diaphanosoma brachyurum, and Cyclops vicinus) over 7 months from lake Suwa, Japan (16); 5, average for four species of mollusks (Assiminea lutea, Nuttalia olivacea, Corbicula japonica, and Laternula limicola) from Gamo lagoon, Japan (30); 6, average for "benthic animals" from the Otsuchi river, Japan (30); 7 and 8, caddis fly larvae from Iliamna Lake and Sashin Creek, AL (13,19) have a trophic position of 4. Finally, quaternary consumers feeding exclusively on tertiary consumers, such as a predator of piscivorous fish, would be calculated as having a trophic position of 5.…”
mentioning
confidence: 99%